(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the linguopoetic analysis of the artistic text, the meanings of words, the appearance of some verbs in the text, linguopoetic features, their relation to the content of the artistic text and their importance are shown.